2016
DOI: 10.1097/aog.0000000000001397
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antenatal Depression Symptoms and Antidepressant Treatment With Preterm Birth

Abstract: In a large cohort of women screened for depression antepartum, those with depressive symptoms had an increased likelihood of preterm and very preterm delivery as well having an SGA neonate. Such risk was not apparent among women who were treated with an antidepressant medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 25 publications
(23 reference statements)
2
25
0
2
Order By: Relevance
“…Third, we were unable to evaluate the treatment received for PTSD, so are unable to comment on how this might modify the association with obstetric complications. There is extensive research and debate over the potential effects of serotonin‐altering medications in pregnancy; whilst we could not explicitly adjust for the use of such medications, the observation that a current PTSD diagnosis but not current depression diagnosis was associated with our outcomes of interest makes it unlikely that this class of medications, which are most commonly used for depression, explains the association. Fourth, as in any observational work there is the possibility of unobserved and residual confounders.…”
Section: Commentmentioning
confidence: 99%
“…Third, we were unable to evaluate the treatment received for PTSD, so are unable to comment on how this might modify the association with obstetric complications. There is extensive research and debate over the potential effects of serotonin‐altering medications in pregnancy; whilst we could not explicitly adjust for the use of such medications, the observation that a current PTSD diagnosis but not current depression diagnosis was associated with our outcomes of interest makes it unlikely that this class of medications, which are most commonly used for depression, explains the association. Fourth, as in any observational work there is the possibility of unobserved and residual confounders.…”
Section: Commentmentioning
confidence: 99%
“…9 In contrast to our findings, a recent study demonstrated an association of a positive screen for depression using Edinburgh Postnatal Depression Scale (EPDS) with preterm birth and SGA, but it noted that such risk was not apparent among women who were treated with an antidepressant medication. 27 The difference in results may be partially explained by methodology since in our study we identified patients with depression or anxiety based on ICD-9 coding and we compared identified patients with depression or anxiety with those who were not unaffected based on the use of psychotropic drugs. In the aforementioned study, patients were identified by EPDS, and all patients who received antidepressants (either screen-positive or screennegative) were compared with all those who did not use antidepressants (both screen-positive and screen-negative).…”
Section: Discussionmentioning
confidence: 99%
“…For example, emotional distress may provoke unhealthy dietary patterns [28] and higher risk of preterm birth and low birth weight [29,30], which are in turn associated with higher risk for both clinical and subsyndromal mental disorders in offspring [31,32,33,34,35,36,37,38,39,40,41,42]. Importantly, subthreshold forms of depression can be identified in preschool children and represent a robust marker of subsequent clinical depression [43].…”
Section: Mental Health Societal Health: Avoiding Mother Blamementioning
confidence: 99%